The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1046/j.1365-3059.1996.d01-130.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between virulence and cytokinin production by Rhodococcus fascians (Tilford 1936) Goodfellow 1984

Abstract: Qualitative and quantitative analyses were made of cytokinins secreted into liquid culture by virulent and avirulent strains of Rhodococcus fascians, and of the endogenous cytokinins in pea plants inoculated with the same strains. Both virulent and avirulent strains secreted a range of cytokinins into liquid culture. The nonhydroxylated cytokinins were present in the liquid cultures at levels up to 1000-fold higher than hydroxylated cytokinins, but the virulent strains secreted only slightly higher levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…In ornamental plants, such infections reduce their value and contribute to economic losses worldwide (Putnam and Miller, 2007). Leafy gall symptoms are reminiscent of CK overproduction and can be partially induced by exogenous application of CKs (Thimann and Sachs, 1966;Eason et al, 1996). Although several CKs have been isolated from R. fascians culture filtrates, a clear correlation with pathogenesis is lacking partially owing to the low concentration of bacterial CKs (Eason et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In ornamental plants, such infections reduce their value and contribute to economic losses worldwide (Putnam and Miller, 2007). Leafy gall symptoms are reminiscent of CK overproduction and can be partially induced by exogenous application of CKs (Thimann and Sachs, 1966;Eason et al, 1996). Although several CKs have been isolated from R. fascians culture filtrates, a clear correlation with pathogenesis is lacking partially owing to the low concentration of bacterial CKs (Eason et al, 1996).…”
mentioning
confidence: 99%
“…Leafy gall symptoms are reminiscent of CK overproduction and can be partially induced by exogenous application of CKs (Thimann and Sachs, 1966;Eason et al, 1996). Although several CKs have been isolated from R. fascians culture filtrates, a clear correlation with pathogenesis is lacking partially owing to the low concentration of bacterial CKs (Eason et al, 1996). A synergistic action by a mixture of bacterially produced CKs has been proposed, leading to persistent accumulation of CKs locally .…”
mentioning
confidence: 99%
“…The shooty phenotype induced by R. fascians on its host plants directed earlier studies toward the synthesis of cytokinins by this bacterium (2,18,24,28,48,51). Nevertheless, careful examination of the various symptoms resulting from R. fascians infection revealed that auxin could also play a role during the interaction with the plant (16,59).…”
Section: Discussionmentioning
confidence: 99%
“…On pFiD188 an isopentenyl transferase (ipt) homologue is located that is essential for symptom development and has been found in all virulent strains examined thus far (14,15,53). Moreover, it is known that R. fascians can produce at least 11 different cytokinins in vitro (2,18,24,28,48,51). In R. fascians, cytokinins probably originate from two sources, either release from tRNA (36, 38) and/or condensation of isopentenyl pyrophosphate and 5Ј-AMP (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation